2011
DOI: 10.1111/j.1365-2613.2011.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexamethasone and testosterone treatment on the regulation of insulin-degrading enzyme and cellular changes in ventral rat prostate after castration

Abstract: Insulin-degrading enzyme (IDE) has been shown to enhance the binding of androgen and glucocorticoid receptors to DNA in the nuclear compartment. Glucocorticoids cause hyperglycaemia, peripheral resistance to insulin and compensatory hyperinsulinaemia. The aim of the present study was to investigate the effect of dexamethasone (D), testosterone (T) and dexamethasone plus testosterone (D + T) on the regulation of IDE and on the remodelling of rat ventral prostate after castration (C). Castration led to a marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Similarly, other studies have shown that testosterone strongly elevates neuronal expression of NEP through an AR-dependent mechanism which in turn decreases Aβ, demonstrated in both castrated rats treated with DHT, and APP23 mice crossed with aromatase knockout mice [104, 105]. Furthermore, testosterone supplementation has been shown to elevate IDE levels in hyperinsulinemic castrated rats [106]. The upregulation of IDE and NEP may also have a beneficial effect on the levels, toxicity or fibrillization of amylin [107, 108].…”
Section: Mechanisms Proposed To Link T2dm and Ad: Testosterone Treatmmentioning
confidence: 86%
“…Similarly, other studies have shown that testosterone strongly elevates neuronal expression of NEP through an AR-dependent mechanism which in turn decreases Aβ, demonstrated in both castrated rats treated with DHT, and APP23 mice crossed with aromatase knockout mice [104, 105]. Furthermore, testosterone supplementation has been shown to elevate IDE levels in hyperinsulinemic castrated rats [106]. The upregulation of IDE and NEP may also have a beneficial effect on the levels, toxicity or fibrillization of amylin [107, 108].…”
Section: Mechanisms Proposed To Link T2dm and Ad: Testosterone Treatmmentioning
confidence: 86%
“…It could be either free insulin accumulated and released or insulin dissociated during chromatography, but the time required for this increment suggested the hormone was actively accumulated into the mitoplasts. We could hypothesize that insulin addition, such as addition of other hormones, increases IDE in mitochondrial matrix with insulin accumulation (Cesar Vieira et al 2011).…”
Section: Mwmentioning
confidence: 99%
“…The imbalance of four plasma hormones associated with the hypothalamic–pituitary–adrenal axis (HPAA), including free triiodothyronine (FT3), free thyroxine (FT4), estradiol (E2), and testosterone (T), is often caused by excess GC. Excess GC also causes deteriorated physical conditions as well as a reduction in body weight and then resulted in enhancement of basic disorders, such as arthritis and diabetes (De Bosscher and Haegeman, 2009 ; Lu et al, 2011 ; Vieira et al, 2011 ; Wang et al, 2015 ; Ferreira et al, 2016 ; Oray et al, 2016 ; Xia et al, 2017 ; Yan et al, 2017 ; Hasona, 2018 ; Panettieri et al, 2019 ). Interestingly, electroacupuncture (EA) has been proven to be an effective therapeutic method to treat GC-induced diseases at the Shenshu (BL23) acupoint which was located adjacent to the second lumbar vertebra on the back (Wang et al, 2015 ; Feng et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%